COMPETITIVE STATE ANXIETY: IMPACT OF POSITIVE SELF TALK TRAINING ON JUNIOR LEVEL FOOTBALL PLAYERS - Abdussalam Kanniyan (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
During the last few decades, coaches and athletes from a wide variety of sports have begun to realize the importance of the mental side of athletic performance. Sport specialists agree that athletic performance is influenced not only by physical skills but also by psychological ones. In order to achieve peak performance athletes need a "total package" including physical skills, psychological skills, fitness and injury prevention (Singh 2011). Study was aimed to examine the effect of Positive Self-Talk training on the Competition anxiety and self-confidence of junior level football players. 36 junior level football players, aged 18.7 ± 2.8 years, were randomly assigned into experimental group and control group. Competitive State Anxiety Inventory-2 (CSAI-2) was used to assess cognitive and somatic anxiety and self-confidence. Positive Self-Talk training was given to the experimental group for 8 weeks. Results of ANOVA revealed significant difference between the pre- test and post test scores of cognitive and somatic anxiety and self- confidence in the experimental group while no significant difference in the control group.